Identifikasi Permukiman Kumuh Studi Kasus: Kawasan Pannampu, Kecamatan Tallo, Kota Makassar - Riska Damayanti; Muh. Ansyari Syamsuddin; Muh. Alfacmy Nurawal (Universitas Muslim Indonesia, 2020)
Makassar City is one of the largest cities in Indonesia with an area of ​​199.3 km² with a population of 1,671,001 people. It has shown itself as a metropolitan city that is able to compete with big cities on the island of Java. Based on the study of the 2017 Makassar City SIAP document, the three dominant slum aspects in Makassar City are 45.36% of the untreated solid waste facility and infrastructure system, 41.09% of the environmental drainage conditions are not according to technical standards and 40.8% of the condition of residential buildings is not yet meet the eligibility standards. The three aspects on average are in the typology of lowland slum, city center, canal banks, river banks, coastal border slums, and there are even slum buildings on the river. The research method used is quantitative and qualitative research with a descriptive approach. The analytical tool used is descriptive analysis by performing a scoring technique. The results of the study were to identify slum areas of Pannampu village from the aspects of building conditions, environmental road conditions, drinking water supply conditions, environmental drainage conditions, wastewater management conditions, solid waste management, and fire protection conditions.